The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1111/j.1365-2184.1976.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic Ratio Requirements for the Initiation of Dna Replication and Fission in Tetrahymena

Abstract: Hydroxyurea (10 mM) arrests the exponential growth of Tetrahymena by blocking DNA replication during S‐phase. After removal of the hydroxyurea (HU), they have a long recovery period during which they are active in DNA synthesis. 3H‐TdR uptake showed that on completion of the recovery period, the cells divide (recovery division) and enter a cell cycle which lacks G1. The frequency, size and DNA content of the extranuclear chromatin bodies (ECB) formed at this division are all markedly increased (2–4) over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Since the macronucleus is engaged exclusively in current service to the cytoplasm, it is not surprising that its replication should somehow be controlled by a size-related feedback mechanism. Thcre are several types of experimental evidence that such a feedback mechanism does exist in ciliates (29,47,66).…”
Section: Relationships Of Clusters Of Cell-cycle Processes: a Minimalmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the macronucleus is engaged exclusively in current service to the cytoplasm, it is not surprising that its replication should somehow be controlled by a size-related feedback mechanism. Thcre are several types of experimental evidence that such a feedback mechanism does exist in ciliates (29,47,66).…”
Section: Relationships Of Clusters Of Cell-cycle Processes: a Minimalmentioning
confidence: 99%
“…7 and 8 underestimate the total increase in macronuclear DNA content in dividing wild-type cells, as the DNA that enters the macronuclear extrusion bodies formed during macronuclear division is not represented. However, extrusion bodies make up a small portion of the total macronuelear DNA in exponentially dividing amicronucleate tetrahymenas (8,66), and observations by Doerder and DeBault, and by Nanney (see reference 12, p. 486), indicate that DNA extrusion occurs infrequently during macronuclear division in exponential phase syngen 1 cells. number increased very little during the first 2 h after the temperature shift, while macronuclear DNA content increased rapidly from the start.…”
mentioning
confidence: 95%
“…Tetrahymena is known to regulate DNA content by altering both the timing and the extent of DNA synthesis. If DNA content is too low, cells go through additional DNA synthesis prior to G2 (Worthington et al 1976), and if DNA content is too high, an S period will be followed by two consecutive cell divisions (Doerder and DeBault 1978). Release of chromatin extrusion bodies may also regulate DNA content (Cleffmann 1980).…”
Section: Discussionmentioning
confidence: 99%
“…These models hold that the cell not only has to attain a certain critical cell size as a prerequisite for cell division but also that arrival at this threshold is sufficient to initiate division (Johnston et al, 1979; Killander and Zetterberg, 1965a,b;Nurse, 1975;Fantes and Nurse, 1977;Prescott, 1960). Since there is a close correlation between ploidy and cell size the parameter effective in the control of cell-cycle events may well be related to the nuclear cytoplasmic ratio (Berger, 1982;Rasmussen and Berger, 1982;Worthington et al, 1976).These models are challenged by the fact that in Tetrahymenu the relationship between cell size and division is uncoupled in the heat-shock synchronisation treatment (Zeuthen and Rasmussen, 1972). Furthermore, recently it was shown that cell division can be induced in the absence of cell growth in mouse 3T3 cells (Zetterberg and Engstrom, 1984), indicating that neither size per se nor increase in mass is an indispensable feature for the initiation of cell division.…”
mentioning
confidence: 96%
“…These models hold that the cell not only has to attain a certain critical cell size as a prerequisite for cell division but also that arrival at this threshold is sufficient to initiate division (Johnston et al, 1979;Killander and Zetterberg, 1965a,b;Nurse, 1975;Fantes and Nurse, 1977;Prescott, 1960). Since there is a close correlation between ploidy and cell size the parameter effective in the control of cell-cycle events may well be related to the nuclear cytoplasmic ratio (Berger, 1982;Rasmussen and Berger, 1982;Worthington et al, 1976).…”
mentioning
confidence: 99%